Design and implementation of an ultra sound distance estimation device - Ng, Waylon Wei Lun. (2013)
In the early days, distance is usually measured by physical means such as using a measuring tape or ruler. Another method is to use ultrasonic distance device which calculate the time interval between the signals sent and received and compute the distance between objects efficiently and the results can be easily read from the display. The most common type of ultrasonic distance measurement device uses the parallax ping where the signal is transmitted from the ultrasonic transmitter to the target and back to the ultrasonic receiver. In this report, a different approach is used to implement the distance measurement by the ultrasonic sensor. The idea is to create two portable ultrasound devices with a pair of ultrasound transmitter and receiver each, place them at two locations and measure the distance. The advantage of this approach is that it does not require timing synchronization and transmission of timing information between locations A and B.